Factores demográficos, académicos, psicológicos, sociales y el estrés de los estudiantes que acuden al comedor universitario, Iquitos 2024 - Lopez Llosa, Delia Aurora (2025)
The objective of this research was to determine the relationship between demographic, academic, psychological, and social factors and stress levels among students attending the university cafeteria in Iquitos in 2024. A quantitative approach was used, with a non-experimental, correlational, and cross-sectional design. The sample consisted of 150 male and female students from the National University of the Peruvian Amazon. Surveys and interviews were conducted using a modified KEZKAK stressors questionnaire and a stress assessment scale. Data were analyzed using the Jamovi statistical software, version 2.3.28 (Spanish). Among the participants, 74.7% were between 18 and 22 years old, and 56.0% were male. Regarding academic factors, 89.3% did not perceive lack of competence as a stressor, and 76.7% did not consider academic overload stressful. For psychological factors, 99.3% did not report helplessness-uncertainty as a stressor, and 91.3% did not perceive emotional involvement as such. In the social domain, 93.3% did not consider the student-teacher relationship to be a stressor, and 95.3% said the same about peer relationships. Bivariate analysis showed a statistically significant relationship between stress levels and academic factors: lack of competence (p < 0.001) and academic overload (p < 0.001); psychological factors: helplessness-uncertainty (p < 0.001) and emotional involvement (p < 0.001); and the social factor: peer relationship (p = 0.003). No significant relationship was found with age (p = 0.872), gender (p = 0.710), or teacher-student relationship (p = 0.072).